Preoperative MRI Evaluation of Relationship between Trigeminal Nerve and Superior Petrosal Vein: Its Role in Treating Trigeminal Neuralgia - Xiong, Nan-Xiang; Zhou, Xiao; Yang, Bo; Wang, Lei; Fu, Peng; Yu, Hua; Wang, Qiangping; Abdelmaksoud, Ahmed; Yuan, Ye; Liu, Weichao; Huang, Yizhi; Budrytė, Kamilė; Huang, Tao; Zheng, Xiaoliang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Objective To assess the value of high-resolution magnetic resonance imaging (MRI) and three-dimensional (3D) reconstruction of the trigeminal nerve and the superior petrosal vein (SPV) in visualizing their anatomical relationship in patients with trigeminal neuralgia (TN).Patients and Methods This study included 97 patients with primary TN who underwent preoperative 3D constructive interference in steady state (CISS) MRI. Image analysis was performed by an independent observer blinded to the operative findings and then compared with surgical data. The 3D reconstruction was assessed dynamically using MIMICS software (Materialise Inc., Leuven, Belgium).Results The 3D relationship between visible structures seen on MRI was consistent with the intraoperative findings in all patients. All cases were divided into three groups by the degree of trigeminal nerve encroachment by SPV. Statistical analysis revealed that the distance from the SPV to the trigeminal nerve was significantly different among the three groups. The diameter of the SPV also differed among the three groups.Conclusion Preoperative 3D imaging provides reliable and detailed information about the intraoperative anatomical relationship between the trigeminal nerve and the SPV. This evaluation is useful for preoperative planning.
Keywords: trigeminal nerve; superior petrosal vein; microvascular decompression; trigeminal neuralgia